2019
DOI: 10.1111/ajad.12896
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Retention in an Outpatient Behavioral Health Clinic With Buprenorphine

Abstract: Background and Objectives Despite high comorbidity between substance use disorders and other mental health diagnoses, there is a paucity of literature on buprenorphine treatment outcomes in outpatient mental health settings. This study aimed to identify rates and predictors of outpatient buprenorphine treatment retention in a Behavioral Health Clinic (BHC). Methods This retrospective cohort study of adults on buprenorphine used multiple logistic regression to identify clinical and demographic factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 27 publications
3
31
1
Order By: Relevance
“…Consistent with this was the lack of evidence for any abuse of stimulants or benzodiazepines in patients who were prescribed these medications. Despite concerns about this that have been raised, 19 use of benzodiazepines in the current study did not appear to put these patients at risk for overdose, which is consistent with the findings of others 3,20 . Stimulant prescription for ADHD in this population also has been found previously to be safe 21 …”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this was the lack of evidence for any abuse of stimulants or benzodiazepines in patients who were prescribed these medications. Despite concerns about this that have been raised, 19 use of benzodiazepines in the current study did not appear to put these patients at risk for overdose, which is consistent with the findings of others 3,20 . Stimulant prescription for ADHD in this population also has been found previously to be safe 21 …”
Section: Discussionsupporting
confidence: 89%
“…Age was the most frequently studied risk factor; of the 31 MMT studies examining age, 18 studies found increasing age to be associated with increased retention [37, 39, 50, 54, 59, 63, 74-76, 80, 81, 83, 89, 92, 94, 95, 97]. Similar patterns were observed for studies of buprenorphine, with eight of 12 included studies reporting increased retention with age [56,58,69,70,72,82,86,93], and mixed OST with four of the six included studies reporting consistent effects for age [43,44,53,87]. While gender was widely studied (n = 40), more than half the studies reported a non-significant association between gender and retention.…”
Section: Plos Onementioning
confidence: 72%
“…While gender was widely studied (n = 40), more than half the studies reported a non-significant association between gender and retention. However, where an association was observed, most studies (12/14) identified men as having significantly lower retention [39,44,50,53,58,63,72,73,90,92,93,97]. Two studies reported opposite effects, one in relation to MMT [66] and Native American (n = 3) [39,50] groups.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…For people with OUDs who do initiate treatment, continued adherence and retention in care are needed to optimize outcomes. Longitudinal studies have consistently found that longterm retention in buprenorphine treatment is poor, with only one-third retained in care at 2 years [145][146][147]. No studies have directly linked stigma to retention in care for opioid agonist treatment, but among persons with other stigmatized conditions like HIV, stigma has been found to be a consistently strong correlate of treatment adherence, retention in care, and treatment outcomes [148,149].…”
Section: Internalized and Anticipated Stigmamentioning
confidence: 99%